Lumped modeling with circuit elements for nonreciprocal magnetoelectric tunable band-pass filter - 李小红 周浩淼 张秋实 胡文文 (Chinese physics B, 2016)
This paper presents a lumped equivalent circuit model of the nonreciprocal magnetoelectric tunable microwave bandpass filter.The reciprocal coupled-line circuit is based on the converse magnetoelectric effect of magnetoelectric composites,includes the electrical tunable equivalent factor of the piezoelectric layer,and is established by the introduced lumped elements,such as radiation capacitance,radiation inductance,and coupling inductance,according to the transmission characteristics of the electromagnetic wave and magnetostatic wave in an inverted-L-shaped microstrip line and ferrite slab.The nonreciprocal transmission property of the filter is described by the introduced T-shaped circuit containing controlled sources.Finally,the lumped equivalent circuit of a nonreciprocal magnetoelectric tunable microwave band-pass filter is given and the lumped parameters are also expressed.When the deviation angles of the ferrite slab are respectively 0° and45°,the corresponding magnetoelectric devices are respectively a reciprocal device and a nonreciprocal device.The curves of S parameter obtained by the lumped equivalent circuit model and electromagnetic simulation are in good agreement with the experimental results.When the deviation angle is between 0° and 45°,the maximum value of the S parameter predicted by the lumped equivalent circuit model is in good agreement with the experimental result.The comparison results of the paper show that the lumped equivalent circuit model is valid.Further,the effect of some key material parameters on the performance of devices is predicted by the lumped equivalent circuit model.The research can provide the theoretical basis for the design and application of nonreciprocal magnetoelectric tunable devices.